Finland Experience in Achieving the Model of Innovative Development and Capabilities of It's Application in Russia - I V Lazanyuk; V V Barabash (Vestnik RUDN. International Relations, 2011)
Theoretic and practical analysis of formation and development of Finland model of innovative development is presented in article. Finland model has more than ten years history. According to the authors, rich Finland experience in the field, developing under the influence of an alliance of private business and the state, can represent scientific and practical interest for the Russian scientific and state heads.